Neat and GNPs loaded natural rubber fibers by electrospinning: Manufacturing and characterization. (25th December 2015) - Cacciotti, Ilaria; House, John N.; Mazzuca, Claudia; Valentini, Manlio; Madau, Francesco; Palleschi, Antonio; Straffi, Paolo; Nanni, Francesca
Abstract: The interest towards natural rubber (NR) is progressively increasing due to its sustainable production and remarkable mechanical properties, presenting a wide application range in the automotive industry and civil engineering. In this paper we report, for the first time, the use of electrospinning technique to produce neat and graphene nanoplatelets (GNPs, 1 wt.%) loaded natural rubber fibers. Both randomly distributed and aligned fibers (average diameter size 1 μm) mats were obtained, resulting uniform and defect-free. A detailed characterization of these fibers is reported, including field emission-scanning electron microscopy (FEG-SEM), X-Ray diffraction (XRD) and infrared spectroscopy (FTIR-ATR) techniques. It has been demonstrated that the electrospinning process is able to induce a strong orientation of the polymeric chains in the case of aligned fibers, with respect to the randomly oriented fibers and solvent cast films. Graphical abstract: SEM micrographs and ATR spectra of random and aligned NR based fibers. Highlights: Natural rubber (NR) fibrous mats loaded with graphene nanoplatelets were successfully fabricated by electrospinning technique. It has been demonstrated that the electrospinning process is able to induce a strong orientation of the polymeric chains. The aligned fibers had remarkably higher dichroic ratio values with respect to the randomly oriented ones.